Development of the second-generation ethanol production process from sisal mucilage - da Silva, Tássia Cristina; Alencar, Bárbara Ribeiro Alves; Soares, Ana Cristina Fermino; Rabelo, Sarita Cândida [UNESP]; de Sá Barreto Sampaio, Everardo Valadares; Albuquerque, Allan Almeida; Menezes, Rômulo Simões Cezar (Elsevier, 2025)
Sisal mucilage (SM) is a lignocellulosic material produced by extracting sisal fiber and passing it through a rotary sieve. It is estimated that only 4 wt% of the Agave sisalana plant is converted into fiber (sisal), while the remaining 96 wt% is discarded as production waste. This study aimed to valorize SM in the production of lignocellulosic ethanol without pretreatment steps. The SM was characterized and showed 39.68 ± 0.32 % cellulose, 13.12 ± 0.22 % hemicelluloses, 6.14 ± 0.5 % lignin, 30.57 ± 0.48 % extractives and 4.11 ± 0.05 % ash. The pre-treatments were harmful for ethanol production, since only lignin was broken down or the cellulose and hemicellulose fractions released HMF, furfural, and acetic acid instead of glucose and xylose. Applying hydrolysis directly on the raw mucilage showed a better response in the extraction of fermentable carbohydrates, after optimization: 101.6 g/L of glucose in enzymatic hydrolysis and 36.12 g/L of glucose in acid hydrolysis. These results agreed with the literature, which reported 100.06 g/L in Agave tequilana under pre-treatment and with enzymatic hydrolysis. The fermentation efficiency of acid and enzymatic routes was 56.86 % (0.04 g ethanol/g biomass) and 71.46 % (0.13 g ethanol/g biomass). This efficiency is a critical parameter in industrial biotechnology, directly impacting production yields, costs, and scalability. Within this context, the present study proved that it was possible to produce ethanol with SM without pretreatment processes. These results indicate opportunities for developing bioenergy value chains that may contribute to development in dry regions.